2000
DOI: 10.1289/ehp.00108399
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III)-induced 8-hydroxydeoxyguanosine in DNA and its reduction by antioxidants: comparative effects of melatonin, ascorbate, and vitamin E.

Abstract: Chromium compounds are well documented carcinogens. Cr(III) is more reactive than Cr (VI) toward DNA under in vitro conditions. In the present study, we investigated the ability of Cr (III) to induce oxidative DNA damage by examining the fonnation of 8-hydrorydeoxyguanosine (8-OH-dG) in calf thymus DNA incubated with CrC13 plus H202. We measured 8-OH-dG using HPLC with electrochemical detection. In the presence of H202, we observed that Cr(III)-induced formation of 8-OH-dG in isolated DNA was dose and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(18 citation statements)
references
References 51 publications
(41 reference statements)
0
16
0
1
Order By: Relevance
“…In vitro, melatonin scavenges hydroxyl radicals, peroxides, singlet oxygen and nitric oxide Tan et al, 2002), and it has been shown that melatonin is superior to vitamin E as a peroxyl radical scavenger (Pieri et al, 1994). Compared with other major antioxidants (ascorbate and vitamin E), melatonin is also 60-and 70-fold more effective, respectively, in reducing oxidative DNA damage (assessed as the production of 8-hydroxy-29-deoxyguanosine) (Qi et al, 2000). Second, melatonin has an indirect effect on the antioxidant machinery by stimulating antioxidant enzymes such as superoxide dismutase, glutathione peroxidase, glutathione reductase, catalase, and other antioxidant molecules, such as ascorbate, trolox and NADH (Gitto et al, 2001), but also by inhibiting pro-oxidant enzymes such as nitric oxide synthase and lipoxygenase Anisimov, 2003;Rodriguez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, melatonin scavenges hydroxyl radicals, peroxides, singlet oxygen and nitric oxide Tan et al, 2002), and it has been shown that melatonin is superior to vitamin E as a peroxyl radical scavenger (Pieri et al, 1994). Compared with other major antioxidants (ascorbate and vitamin E), melatonin is also 60-and 70-fold more effective, respectively, in reducing oxidative DNA damage (assessed as the production of 8-hydroxy-29-deoxyguanosine) (Qi et al, 2000). Second, melatonin has an indirect effect on the antioxidant machinery by stimulating antioxidant enzymes such as superoxide dismutase, glutathione peroxidase, glutathione reductase, catalase, and other antioxidant molecules, such as ascorbate, trolox and NADH (Gitto et al, 2001), but also by inhibiting pro-oxidant enzymes such as nitric oxide synthase and lipoxygenase Anisimov, 2003;Rodriguez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the toxicological literature (Qi et al 2000) has suggested that bioavailable Cr(III) induces DNA damage. While the most common chromium oxides, e.g., Cr 2 O 3 , have very low solubility in water, toxicological studies have shown evidence of deep translocation of ultrafine particles, as well as leaching of metal that contributes to the toxicity of these particles (Veranth et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An antidepressant which helps in prevention of obesity and type 2 diabetes mellitus by preventing appetite in insulin resistance and glucose intolerance as well as regulation of body composition [2,3]. While chromium intake is crucial in optimal energy metabolism and regulation excess consumption has been reported to accumulate intracellular Cr3+ ions that may lead to long-term genotoxic effects by formation of covalent bonds to DNA [4]. Taken together, cytotoxic, genotoxic and mutagenic effects as well as activity damaging to the mitochondria and induction of apoptosis have been reported for CrPic using mammalian cell cultures [5,6].…”
Section: Introductionmentioning
confidence: 99%